Critical illness myopathy in intensive care patients: Pathogenetic concepts and clinical management - Friedrich, Oliver; Hund, Ernst (Anaesthesist, 2006)
Intensive care patients are at increased risk of developing sepsis with multi-organ failure during treatment (severe sepsis) possibly leading to complications of the central and peripheral nervous system. Among these, septic encephalopathy, critical illness polyneuropathy (CIP) and critical illness myopathy (CIM) are the most important. Neuromuscular complications in particular are difficult to diagnose as they mostly become apparent only when sedation has ceased and the awakening patient experiences difficulties in weaning from the respirator and reduced voluntary strength. CIP and CIM are generally self-limiting, however, they greatly prolong ICU stay and rehabilitation, thus nowadays also imposing a real budget threat. The diagnostics, especially the differentiation between CIM and CIP is difficult and a multi-disciplinary approach involving ICU physicians, anesthetists and neurologists is needed. Our knowledge of the causes of the primary ICU myopathy, although rapidly evolving during recent years, is still in its infancy and specific treatment of CIM is not yet available. The present overview summarizes insights into clinical and new diagnostic strategies for early detection of neuromuscular dysfunction in ICU patients. This article focuses on current concepts and results revealing the pathomechanism(s) of CIM and some simple therapeutic or preventive measures have been deduced which are summarized and discussed. © 2006 Springer Medizin Verlag.
Keywords: Antioxidative capacity; Critical illness; Insulin therapy; Myopathy; Pathomechanisms